Investigations into insect-induced plant responses of water hyacinth (Eichhornia crassipes (Mart.) Solms-Laub.) (Pontederiaceae) - May, Bronwen (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
The water hyacinth (Eichhornia crassipes (Mart.) Solms-Laub (Pontederiaceae)) biological control programme makes use of tight plant-insect interactions to control the weed, by reestablishing the interactions between the plant and its natural enemies. Since the beginning of the water hyacinth biological control initiative, the impact of biological control agent herbivory on water hyacinth's population growth and fitness have been well documented; however, very few investigations have been conducted to determine whether herbivory elicits insect-induced responses by water hyacinth. Studies were conducted to determine the presence and function of water hyacinth insectinduced responses, using the plant activator, BION®, in attempt to determine the plant hormone-mediated pathways regulating the final expressions of insect-induced defences in response to herbivory by the phloem-feeder, Eccritotarsus catarinensis (Carvalho) (Hemiptera: Miridae) and the leaf chewer, Neochetina bruchi Hustache (Coleoptera: Curculionidae). BION® (Syngenta, acibensolar-S-methyl (benzothiadiazole)) is a dissolvable, granular formulation that contains a chemical analogue of the plant hormone, salicylic acid (SA), which typically regulates defences against pathogens. The application of BION® results in the induction of the SA-mediated defence pathways in plants (activation of defences against pathogens), and consequently the inhibition of the jasmonic acid (JA)- mediated defence pathways (de-activation of defences against insect herbivores). To test for induced defence responses in water hyacinth, plants treated with BION® and then subjected to herbivory, were compared to un-treated plants that were also subjected to herbivory, BION®-only treated plants and control plants. The application of BION® did not confer resistance against the two insect herbivores, as herbivory, reductions in chlorophyll content and plant growth (leaf production and second petiole lengths) significantly increased in comparison to non-BION® treated plants. Furthermore, palatability indices significantly increased (>1.00) in BION® treated plants, reflecting increased weevil preferences for SAinduced water hyacinth plants. This concluded that SA-mediated defences are not effective against insect herbivory in water hyacinth plants, but are in fact palatable to insect herbivores, which reflects ecological and physiological costs of SA-mediated defences (pathogen defences) in water hyacinth. Biochemical analyses of leaves exhibited increases in nitrogen content in BION® treated plants. These elevated levels of nitrogenous compounds account for the increases in mirid and weevil preferences for BION® treated plants. The increases in nitrogenous compounds are probably structural proteins (e.g. peroxidises), because leaves treated with BION® increased in toughness, but only when exposed to herbivory. Regardless, insect herbivory was elevated on these leaves, probably because the nitrogenous compounds were nutritionally viable for the insects.
Keywords: Water hyacinth; Water hyacinth -- Biological control; Water hyacinth -- Defenses; Aquatic weeds; Insect-plant relationships; Miridae; Curculionidae